2007
DOI: 10.1111/j.1447-0594.2007.00389.x
|View full text |Cite
|
Sign up to set email alerts
|

Lower urinary tract symptoms (LUTS) in people aged 50 or older consulting general practitioners

Abstract: The incidence of lower urinary tract symptoms (LUTS) in people consulting general practitioners (GPs) was investigated. We used a questionnaire including seven questions regarding LUTS and one question regarding bothersomeness based on the International Prostate Symptom Score (I-PSS), three questions on the Overactive Bladder Symptom Score (OABSS) and four questions on the International Consultation on Incontinence Questionnaire Short-Form (ICIQ-SF), and conducted the survey among 1120 people aged 50 or older … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…For the IPSS, scoring ranges from 0 (no symptoms) to 35 (maximal symptoms). LUTS severity was classified into three categories: mild (0-7), moderate (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) and severe (20-35) and for the QoL index, the range is 0 (delighted) to 6 (terrible) [16]. The storage subscore was defined as the sum of scores for questions 2, 4 and 7 on the IPSS and the voiding subscore was the sum of scores for questions 1, 3, 5 and 6.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the IPSS, scoring ranges from 0 (no symptoms) to 35 (maximal symptoms). LUTS severity was classified into three categories: mild (0-7), moderate (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) and severe (20-35) and for the QoL index, the range is 0 (delighted) to 6 (terrible) [16]. The storage subscore was defined as the sum of scores for questions 2, 4 and 7 on the IPSS and the voiding subscore was the sum of scores for questions 1, 3, 5 and 6.…”
Section: Methodsmentioning
confidence: 99%
“…A similar self-administered questionnaire survey was conducted among men and women aged ≥ 50 years consulting GPs for various chronic medical problems. The original survey conducted between July and August 2005 was also approved by Institutional Review Board and 958 people participated after informed consent was obtained [12]. Finally, the data from 330 men and 418 women who completed all questions were available for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…We believe that urologists should know of such an association, when educating GPs as to the LUTS practice. Here, we demonstrate the relationship between LUTS and health‐related (HR)‐QOL among 330 men (mean age: 67 ± 9) and 418 women (68 ± 9), using the Japanese versions of the International Prostate Symptom Score (I‐PSS), the Overactive Bladder Symptom Score (OABSS), the International Consultation on Incontinence Questionnaire–Short Form (ICIQ‐SF) and King's Health Questionnaire (KHQ) 1,2 …”
Section: Relationships Among I‐pss Oabss Iciq‐sf Qol Index and Khqmentioning
confidence: 95%
“…Several researchers also reported that the incidence of LUTS increases with aging 1–5 . According to our previous questionnaire survey, approximately one‐third of men and women aged 50 years or older who consulted general practitioners (GPs) for medical problems had some LUTS and it was thought that they required evaluation by a GP 6 …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] According to our previous questionnaire survey, approximately onethird of men and women aged 50 years or older who consulted general practitioners (GPs) for medical problems had some LUTS and it was thought that they required evaluation by a GP. 6 To improve the clinical practice for LUTS by GPs, we developed a manual for use in Japan. 7 However, Hammond et al indicated that the education strategy using pamphlets and face-to-face staff consultations had no measurable impact.…”
Section: Introductionmentioning
confidence: 99%